The Acceptance of Buyer to the Greenhouse Residency Concept - Mohd Nazaruddin Yusoff; Kamarudin Ngah; Azlizan Talib; Mohd Fitri Abdul Rahman (International Journal of Supply Chain Management, 2016)
The public nowadays has become more aware on the environmental issue. This is because they have understood the negative impact of pollution and wasting of natural resources to human being and also the Mother Nature. The conventional housing area that has been built to fulfil the basic needs of housing to the community in Malaysia was seen as a negative type of development to environment. This is because the abundance use of energy and thus high amount of carbon dioxide release to the atmosphere. In order to handle this problem, the greenhouse resident concept has been introduced. This concept can reduce utilization of energy, water, and natural resources but still can give good quality of air and importantly the comfort of the occupant. But, how much do the public especially house buyer knows and understands about the concept of greenhouse resident because it is relatively new trend in the home development in Malaysia. This research is done to evaluate the level of knowledge among the house buyers in the concept, components, and the challenges in developing green house residence in Malaysia.